The histology of the alimentary canal and associated structures of Metopolophium Dirhodum (Homoptera : Aphididae) - Campbell, M. B. S. C.(Mark Bryer St Clair) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1985.